Midwifery Care Management for Ms. K with Primary Dysmenorrhea at RSI Sitti Khadijah 1 Makassar: Manajemen Asuhan Kebidanan Remaja Pada Nn â€Kâ€ dengan Gangguan Dismenore Primer di RSI Sitti Khadijah 1 Makassar - Rosdiana; Firdayanti; Andi Dian Diarfah (Jurnal Midwifery, 2023)
Introduction Adolescence is a transitional period from childhood to adulthood with an age range of 12-21 years. During this period, a maturation process occurs in terms of physical, biological, and psychological. In adolescence period, the mental and physiological aspects of individual were yet to be mature. As a result, many adolescents may experience dysmenorrhea that could ufortunately affect their daily activities, including learning activities. Method The method used in this study was a case study research by employing the 7-stage of Varney management approach and SOAP documentation procedure. Location at the hospital of Sitti Khadijah 1 Makassar. Result The findings of this research indicated that the 19-year-old patient complained of lower abdominal pain penetrating her back. She experienced this condition for 3 days for more than 6 times. Furthermore, she was also anxious with her abdominal tenderness and tension. From this research, the ultrasound examination showed no signs of abnormalities. Thereofore, the treatment was carried out by administering the anti-pain medication, mafenamet acid and non- pharmacological ginger ingredients. Conclusion This study concluded that varios examinations were given to the patient. From the results of her physical examination, the abdomen was identified to be in pain. However, there were no complications found in the patient, and the abdominal pain was no longer felt after the treatments were given. As implications, it is expected that midwives are able to provide care for patients with primary dysmenorrhea by providing proper explanations and appropriate treatment to patients. In addition, Islamic therapy should also be provdied so that patients could feel relax and calmer.